Responsabilidade social em arranjos produtivos locais: a prática do APL de confecção de Nova Friburgo e região - Roedel, Daniel (2009)
This dissertation intends to present an analysis about the proposition of social responsibility actions in micro and small companies leaded by the cluster governance. The nature of this subject is close to the sustainable development concept, understood as alternative for economic and social insertion in an environment that the globalization of markets under neoliberalism has predominated. For field research, the cluster of fashion lingerie in Nova Friburgo and region, in Rio de Janeiro, was chosen. The high level of informality that predominates in these companies, besides the residues produced, strengthens the interest in knowing the scope of social responsibility practices. The hypothesis is that current actions are not consolidated in the governance orientation, not even are a mandatory way to the sustainable development in that region.